Climatic Conditions and Flowering Season in Outer Himalayas at Nainital - Gupta, Raj Kumar (Indian Forester, 1961)
Correlation between the climatic conditions and flowering periodicity for the outer Himalayas is worked out in respect of Nainital. Climatic conditions have been represented by factors like temperature, dryness and xerothermic index, based on the principles advocated by Prof. Gaussen of Toulouse University. Climate of Nainital is represented by the formula t3S2X1.